2001
DOI: 10.1001/jama.286.15.1869
|View full text |Cite|
|
Sign up to set email alerts
|

High-Dose Antithrombin III in Severe Sepsis

Abstract: High-dose antithrombin III therapy had no effect on 28-day all-cause mortality in adult patients with severe sepsis and septic shock when administered within 6 hours after the onset. High-dose antithrombin III was associated with an increased risk of hemorrhage when administered with heparin. There was some evidence to suggest a treatment benefit of antithrombin III in the subgroup of patients not receiving concomitant heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
287
0
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,248 publications
(313 citation statements)
references
References 52 publications
7
287
0
10
Order By: Relevance
“…Guidelines for use in various countries do not recommend the use of antithrombin based on the results of a large‐scale clinical trial (the KyberSept trial) 390. In contrast, antithrombin replacement therapy is often used in patients with sepsis‐associated DIC in Japan.…”
Section: Cq16: Diagnosis and Treatment Of Disseminated Intravascular mentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for use in various countries do not recommend the use of antithrombin based on the results of a large‐scale clinical trial (the KyberSept trial) 390. In contrast, antithrombin replacement therapy is often used in patients with sepsis‐associated DIC in Japan.…”
Section: Cq16: Diagnosis and Treatment Of Disseminated Intravascular mentioning
confidence: 99%
“…However, there is currently no unified view regarding the efficacy of these drugs. One reason for this is that in the United States and European countries, the clinical utility of various anticoagulants has been studied primarily in large‐scale randomized controlled trials (RCTs) involving patients with severe sepsis 390, 391. These studies did not focus on sepsis‐associated DIC, and the anticoagulant therapies administered to the participants of these studies clearly differed from those used in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…However, in sepsis‐induced DIC, a decrease in AT activity is frequently observed27, 28, 29, 30 and is associated with high mortality rates 31, 32. Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4.…”
Section: Antithrombinmentioning
confidence: 99%
“…Several RCTs to investigate the effects of high‐dose AT administration in patients with sepsis have been carried out 4, 33, 34, 35, 36. Although some RCTs indicated benefits of high‐dose AT administration in patients with sepsis,33, 34, 35 a large RCT (the KyberSept trial) failed to show any survival benefits 4. However, a subgroup analysis of the KyberSept trial indicated that AT administration significantly improved survival rates in patients with sepsis‐induced DIC 9…”
Section: Antithrombinmentioning
confidence: 99%
See 1 more Smart Citation